Comparison of Disulfiram and Naltrexone in Cases of Alcohol Dependence Syndrome - Adhikari, Sandarba; Tulachan, Pratikchya; Ojha, Saroj Prasad; Chapagai, Manisha; Dhungana, Saraswati; Pant, Sagun Ballav (Journal of Nepal Health Research Council, 2020)
Background: Relapse prevention in alcoholism is recognised as an important component of management. Use of pharmacotherapies to prevent relapse in combination to psychological intervention is emerging. Disulfiram and Naltrexone are two of three FDA approved drugs for pharmacotherapy. The aim of the study is to compare the effectiveness of these two drugs in preventing relapse in alcohol dependence syndrome cases. Methods: A prospective crossectional study was conducted to compare disulfiram and naltrexone in alcohol dependent patients in tertiary institution. Cases of alcohol dependence syndrome were diagnosed based on ICD-10 DCR presenting to psychiatry department of Tribhuvan University Teaching Hospital, over the period of 6 months. After detoxification and fulfillment of inclusion criteria, semi structured proforma, Severity of alcohol dependence questionnaire, Stages of change readiness and treatment eagerness scale, Obsessive compulsive drinking scale were applied. Drug allocation was based on simple random method and on subsequent follow ups done at 2nd, 4th, 8th, 12th week semi structured proforma, Obsessive Compulsive Drinking Scale were completed and psychological intervention continued. After data collection, analysis and final results were computed.Results: Both drugs reduced craving (p<0.001) and amount of alcohol intake (p<0.001). Relapse was more in naltrexone group but was not statistically significant (p>0.05). Side effects were more with disulfiram (p<0.001) whereas dropout was more in naltrexone group, (p<0.01).Conclusions: Disulfiram and Naltrexone were equally effective in reducing craving, reducing amount of alcohol intake, and preventing relapse in 12 weeks follow up period. Naltrexone was found to be better in tolerability whereas disulfiram was better in terms of dropout from treatment. Keywords: Alcohol dependence; disulfiram; naltrexone; relapse